The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/inorganics5040082
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Surface-Oxidized Mixtures of 2LiBH4 + Al/Additives (TiF3 or CeO2)

Abstract: Abstract:Research for suitable hydrogen storage materials is an important ongoing subject. LiBH 4 -Al mixtures could be attractive; however, several issues must be solved. Here, the dehydrogenation reactions of surface-oxidized 2LiBH 4 + Al mixtures plus an additive (TiF 3 or CeO 2 ) at two different pressures are presented. The mixtures were produced by mechanical milling and handled under welding-grade argon. The dehydrogenation reactions were studied by means of temperature programmed desorption (TPD) at 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…They identified the formation of Al 2 O 3 and Ti 2 O 3 during decomposition of TiCl 3 -doped NaAlH 4 and attributed the enhanced dehydrogenation kinetics to the high hydrogen mobility within these oxides species near the surface. Kato et al and Carrillo-Bucio et al both found that partial oxidation of milled LiBH 4 , either with oxygen or oxide additives and limited to the surface, reduced the activation barrier for dehydrogenation, lowering the observed T dec . , The oxidized samples exhibited additional Li 2 O by XPS following segregation of lithium to the surface, which helped to destabilize LiBH 4 for hydrogen desorption and not release of diborane. These studies suggest that the role of surface oxidation on metal hydride hydrogenation and dehydrogenation kinetics may be far more subtle and complex than has generally been supposed.…”
Section: Mechanistic Effects Of Nanosizingmentioning
confidence: 99%
“…They identified the formation of Al 2 O 3 and Ti 2 O 3 during decomposition of TiCl 3 -doped NaAlH 4 and attributed the enhanced dehydrogenation kinetics to the high hydrogen mobility within these oxides species near the surface. Kato et al and Carrillo-Bucio et al both found that partial oxidation of milled LiBH 4 , either with oxygen or oxide additives and limited to the surface, reduced the activation barrier for dehydrogenation, lowering the observed T dec . , The oxidized samples exhibited additional Li 2 O by XPS following segregation of lithium to the surface, which helped to destabilize LiBH 4 for hydrogen desorption and not release of diborane. These studies suggest that the role of surface oxidation on metal hydride hydrogenation and dehydrogenation kinetics may be far more subtle and complex than has generally been supposed.…”
Section: Mechanistic Effects Of Nanosizingmentioning
confidence: 99%
“…In addition, the surface oxidation effects help to reach thermodynamically predicted temperatures for dehydrogenation reactions. 40,42,43 In this study, it is observed that mesoporous NiCo 2 O 4 with a surface oxidized LiBH 4 system presents an outstanding storage performance. Notably, 5.8 wt% of hydrogen was desorbed using a LiBH 4 + 75% NiCo 2 O 4 system in isothermal dehydrogenation at 250 °C for 60 minutes.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, Al has been popularly employed as another destabilization agent to improve the hydrogen desorption properties of LiBH 4 . The Al source can be either a metallic Al or a complex hydrides containing Al [24][25][26]. However, the metallic Al is usually coated with an oxide layer, which greatly limits the improvement of dehydrogenation and the reversibility of LiBH 4 .…”
Section: Introductionmentioning
confidence: 99%